Botulinum toxin A complex exploits intestinal M cells to enter the host and exert neurotoxicity - Matsumura, Takuhiro (Nat Commun, 2015)
To cause food-borne botulism, botulinum neurotoxin (BoNT) in the gastrointestinal lumen must traverse the intestinal epithelial barrier. However, the mechanism by which BoNT crosses the intestinal epithelial barrier remains unclear. BoNTs are produced along with one or more non-toxic components, with which they form progenitor toxin complexes (PTCs). Here we show that serotype A1 L-PTC, which has high oral toxicity and makes the predominant contribution to causing illness, breaches the intestinal epithelial barrier from microfold (M) cells via an interaction between haemagglutinin (HA), one of the non-toxic components, and glycoprotein 2 (GP2). HA strongly binds to GP2 expressed on M cells, which do not have thick mucus layers. Susceptibility to orally administered L-PTC is dramatically reduced in M-cell-depleted mice and GP2-deficient (Gp2(−/−)) mice. Our finding provides the basis for the development of novel antitoxin therapeutics and delivery systems for oral biologics.